Evaluation of Learning Management System for Users with Accessibility Needs Using Extended Technology Acceptance Model (E-TAM) - Zatin Niqotaini; Henki Bayu Seta; Theresiawati; Dwi Vernanda; Artika Arista; Muhammad ibrahim Al Farisi; Rapolo Joshua Napitupulu (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Inclusive education aims to provide equal learning opportunities for students with special needs, including the use of a Learning Management System (LMS). The urgency of this research stems from the significant challenges in LMS accessibility, which pose major obstacles for students with disabilities. These challenges include difficult navigation, a lack of screen reader features, and unfriendly interface design. The objectives of the research are to identify and evaluate the factors of LMS acceptance by students with disabilities and provide recommendations. The method uses the Extended Technology Acceptance Model (E-TAM) to identify factors influencing the acceptance of LMS by students with disabilities, such as perceived usefulness, perceived ease of use, and external factors. The findings indicate that System Quality (SQ) has no significant influence on Attitude Toward Using (AT), with the estimated effect size being 1.4%. As an implication, the institutions need to provide easy-to-follow guides to help users with disabilities.